MEASUREMENT METHOD OF ultrahigh own Q-factor of the superconducting cavity BASED on electron beam Excitations - A. A. Kurayev; S. V. Kolosov; A. K. Sinitsyn (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The precise method of measurement of ultrahigh own Q-factors of the superconducting cavity, based on excitation of oscillations in the cavity by an electronic beam is offered. At such measurement the resonator is not coupled to any external microwave chains, its own Q-factor is determined on a power loss of an electronic beam which can be measured with a high accuracy.